The Path to Fully Representational Theory of Mind: Conceptual, Executive, and Pragmatic Challenges - Pesch, Annelise; Semenov, Andrei D.; Carlson, Stephanie M. (Frontiers in Psychology, 2020)
Although an explicit Theory of Mind (ToM) has been found to develop around 4 years of age in Western societies, recent work showing that 4- and 5-year-olds fail modified versions of False Belief tasks as well as seemingly easier True Belief tasks calls into question the robustness of preschoolers’ belief understanding. Some have argued these findings illustrate children’s conceptual limitations in their understanding of belief that are masked by standard False Belief tasks. However, others claim these examples of children’s failure can be explained by pragmatics of the testing situation, rather than conceptual limitations. Given the documented relation between ToM and executive function, an unexamined possibility is that children’s failure can be explained by certain executive demands. In the current study, we examined the relation between typically developing 4- (n = 43) and 5-year-olds’ (n = 42) performance on traditional and modified False Belief tasks, True Belief tasks, and one component of executive functioning - working memory. We found that children performed worse on modified False Belief tasks and True Belief tasks compared to standard 2-option False Belief tasks, and that working memory was related to modified 3-option contents False Belief performance. These results suggest that a fully representational ToM, one that is stable in the context of increased conceptual, executive, and pragmatic demands, may develop later than traditional accounts have assumed.